Employee participation in the private sector in Malaysia: The Applicability of Favourable Conjunctures Model - Parasuraman, Balakrishnan; Kelly, Di; Rathakrishnan, Balan (ASEAN Marketing Journal, 2021)
EP is one crucial aspect of the employment relationship in both private and public organisations in many countries. In 2001, Poole, Lansbury and Wiles developed a model for comparative EP, which they named the Favourable Conjunctures Model. So far, this model has only been applied in developed countries such as the United States of America, United Kingdom, Australia and Europe. There it was applied in order to examine worker participation from the national perspective. No extensive study has been conducted using this model to explain worker participation practices at the company level. In parallel with this aspect, this model also has never been used to explain the nature of EP in the Asian developing countries. This current research will use the Favourable Conjunctures Model to examine the nature of EP in private enterprises based on empirical study carried out in Malaysia. The argument of this paper is that the Favourable Conjunctures Model of Industrial Democracy (Poole et al. 2001) is inadequate to elucidate the characteristics of EP in Malaysia. Based on empirical findings from three private companies in Malaysia, the paper argues that there are many contextual factors that influence the nature of EP in Malaysian private companies that are not taken into account by the model. They are:multi-ethnic (cultural) influences, the repressive role of state in the Malaysian industrial relations, the New Economic Policy and industrialisation plan, Islamic working ethics, the influence of a British colonial history, lack of training among non-managerial employees in EP, the impact of foreign direct investment on industrial relations, to identify a few. Based on this study, it is proposed that the present Favourable Conjunctures Model of Industrial Democracy (Poole et al. 2001) be modified based on the contextual factors discussed above. The paper concludes that the western model of EP could not be directly applied in Malaysia without some adjustment of the model.